Fostering the Human Rights of Migrant Children Through Art and Educational Practices at the United States-Mexico Border - Jorge Francisco Sánchez-Jofras; Pablo Treviño-Rodríguez; Maya Polanco (Studies in Social Justice)
This paper explores the impact of art and educational practices on fostering the psychosocial well-being and human rights awareness of migrant children residing in shelters at the U.S.-Mexico border. This population often faces acute vulnerabilities due to migratory status and exposure to trauma during transit, including violence, displacement, and family separation. The study emphasizes the collaborative efforts of nongovernmental organizations (NGOs) and early childhood educators within these shelters. Data collection entailed conducting interviews with early childhood educators, art instructors, and literacy mediators who work directly with migrant children. Observations were carried out in reading rooms and multilevel classroom settings, focusing on the structure and flow of activities to ensure they addressed the emotional and psychological needs of the children involved. This research is situated against the backdrop of migrant families and children entrapped at the U.S.-Mexico border due to the Remain in Mexico and Title 42 policies implemented during the COVID-19 pandemic and its aftermath. These policies have resulted in prolonged stays in shelters for asylum-seeking families, creating environments characterized by immigration uncertainty, limited resources, and emotional strain. The findings illuminate the effectiveness of art and educational practices and the crucial role of early childhood educators in helping children process trauma, express their emotions, and develop a sense of identity and agency amidst challenging circumstances.